Bilateral Congenital Ectropion Uveae and Glaucoma - Siddharth Madan; Rajiv Garg (Delhi Journal of Ophthalmology)
The presence of congenital ectropion uveae (CEU) in a patient calls for a definitive work-up for underlying glaucoma as the latter if missed can have potentially blinding sequel. Most patients may not be aware of the presence of CEU as far as third to fourth decade and may have lost significant proportion of their visual fields at their first ophthalmic consultation. A case of bilateral CEU with bilateral glaucoma is described emphasizing this association.